Peripheral primitive neuroectodermal tumour – a rare cause of a popliteal fossa mass: A case report and review of the literature - Davis, Colin M (Pulsus Group Inc, 2014)
A literature review of peripheral primitive neuroectodermal tumours, illustrated with an index case report describing an 80-year-old woman who presented with a mass in the left popliteal fossa, is reported. An excision biopsy was performed, revealing a possible peripheral primitive neuroectodermal tumour as the primary pathology. Normally confined to the chest wall and axial soft tissues of children and young adults, reports of this tumour existing in other areas and in the elderly population are scarce.